Biomass production and resource partitioning in silvi-pastoral systems - Suman Jacob George (College of Forestry, 1993)
A randomized block design experiment involving factorial combinations of four fodder species : Pennisetum purpureum (hybrid napier), Brachiaria ruziziensis (congo signal), Panicum maximum (guinea grass) and Zea Mexicana (Teosinte) and four tree species (Leucaena leucocephala, Casuarina equisetifolia, Acacia auriculiformis and Ailanthus triphysa initiated in June 1988 was used for the present investigations. The study was pursued with the objective of quantifying the biomass production potential of selected forage species grown in association with tree components after canopy closure, comparing the productivity of different tree components grown in silvopastoral systems; characterizing the micro-site enrichment and nutrient cycling aspects of silvopastoral systems, analysis the partitioning of solar radiation among the different components of the system and elucidate influence regarding the nature of root interactions in silvopastoral systems.